Autoimmune Neutropenias: Update on Clinical and Biological Features in Children and Adults. Issue 1 (19th January 2023) - Fioredda, Francesca; Dufour, Carlo; Höglund, Petter; Papadaki, Helen A; Palmblad, Jan
Abstract : The definition of autoimmune neutropenias (AIN) has been based on the demonstration of autoantibodies directed to various epitopes on blood neutrophils. However, this definition is probably too limited and excludes neutropenias (NPs) with a negative autoantibody test but with other phenomena that indicate an underlying autoimmune process. Examples of such AINs may be complete or incomplete systemic lupus erythematosus or other autoimmune diseases where NP is common but patients may not fulfill formal diagnostic criteria for a rheumatic disease. Recently, various inherited immune-dysregulation syndromes, such as those related to variants in, for example, TACI, BAFFR, ACKR1/DARC, LRBA, CTLA 4 genes, with dysregulated B- and T-lymphocyte functions, have been associated with concomitant AINs. Cellular immune mechanisms may also play a prominent role in the development of NP, in the presence or not of autoantibodies, in cases of large granular lymphocyte syndromes of T- and NK-cell types or in chronic idiopathic NP, particularly in adults with T-cell clonal populations. The course of AIN may differ according to age, being transient and rather uncomplicated in children, and chronic with treatment requirement in adolescents and adults. This review discusses current knowledge of AINs, including diagnostic procedures, treatments, and prognosis.